Gambaran - Riswari, Rizki Mustika (Jurnal Informasi Kesehatan Indonesia (JIKI), 2021)
According to Presidential Regulation No. 12 of 2013 concerning Health Insurance, patient satisfaction is a key indicator of the standard of a health facility and the low quality of service satisfaction will have an impact on the number of visits that will affect the profitability and health facilities. Measurement of patient satisfaction is an important element in providing better, more efficient and more effective services. The level of patient satisfaction with services is an important factor that develops a service provider system that is responsive to patient complaints, minimizes costs and time and maximizes the impact of services on patients. The purpose of this study was to determine the general picture of patient satisfaction in terms of the servqual method using five indicators namely responsiveness, assurance, physical evidence, attention, and reliability as well as the level of quality of service at Aisyiyah Islamic Hospital Malang. Case study approach through questionnaire. Subjects were JKN hospitalized patients, a sample of 30 respondents who were determined by the Purposive Sampling method. Data that has been analyzed are presented in tabular form and accompanied by an explanation. This research was conducted for 3 days. Based on the research, it was found that JKN hospitalized patients at Aisyiyah Islamic Hospital Malang were quite satisfied with the services provided with an average satisfaction rating of 84.5%. With an assessment using five indicators, the average value of respondents 'answers shows the average value of respondents' answers to responsiveness indicators of 82.5%, guarantee indicators 85.667%, indicators of physical evidence by 84%, indicators of concern by 84.667%, and indicators of reliability by 85.5%. From this study it can be concluded that although the satisfaction rate is still 84.46%, JKN hospitalized patients are quite satisfied with the services provided by hospital staff both by doctors, nurses, and also hospital staff Keywords: Quality, Satisfaction, JKN inpatients.